Microbial, immunological and histopathological studies on the effects of probiotic and Phaleria macrocarpo leaves extract in immunocompromised New Zealand white rabbits (IR) - Saleh, Imad Dawood (2018)
The purpose of this study is to investigate the advantages of using a novel formulated probiotic and Phaleria macrocarpa leaves extract on immunocompromised New Zealand White (NZW) rabbits. Forty rabbits were divided into four groups; three group were induced with immunosuppressant drug (Azathioprine, at 500 mg/kg/day) and the forth group served as control. The first group of immunocompromised rabbits treated with the formulated probiotic, the second group with P. macrocarpa extract, while the third group without any treatment. The results were assessed through two different period of time; induction period (14 days) and treatment period (14 days). Results showed that Feed Conversion Ratio (FCR) of immunocompromised groups were decreased significantly (P0.05) during the induction period; -2.07 for the non-treated, -1.06 for treated with the probiotic, and -2.54 for the treated with P. macrocarpa extract, compared to control group (1.34). However, during the treatment period, the FCR continued decreased (insignificantly) within the non-treated group (as -8.99), but increased significantly in both probiotic treated group (0.70), and extract treated group (0.66), compared to control (1.49). The microbiological and immunological findings indicated that treatment with P. macrocarpa extract enhanced the rabbits to maintain significantly the full blood cells count (9.160.39x109) closer to normal levels of control group (9.680.30x109), in comparison to probiotic treated group (5.422.20x109) and non-treated group (3.200.59x109). The percentage of lymphocytes were decreased significantly in the extract treated group (32%), probiotic treated (25%), and non-treated (20%), compared to control group (66%). The histopathological findings declared critical changes occurred to the colon tissue of non-treated rabbits, including loss of regular mucosal folds, variable degrees of mucosal edema and congestion, submucosal hemorrhage, accumulative score of colon gross anatomy, and substantial serious lesions. Meanwhile, most of these histopathological changes were highly maintained in treated rabbits, either with P. macrocarpa extract or with the formulated probiotic. As a conclusion, the daily uptake of P. macrocarpa extract or the formulated probiotic could improve significantly (both specific and nonspecific) immune responses of immunocompromised rabbits, and maintain the damaged colon tissue (caused due to the immunosuppressant drug). The study implicates that the formulated probiotic and P. macrocarpa extract products can serve as supplements in reducing medical complications of domesticated animals or human patients under certain condition.